PENGARUH GAYA KEPEMIMPINAN, PROFESIONALISME, DAN KEPUASAN KERJA TERHADAP KINERJA PEMERIKSA PAJAK (Studi Pada Pemeriksa Pajak di KPP Madya Pekanbaru, KPP Pratama Pekanbaru Tampan, dan KPP Pratama Pekanbaru Senapelan) - Ridho Kurniawan; Vince Ratnawati; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aims to examine the effect of leadership style, professionalism, and job satisfaction to the tax auditors performance at KPP Madya Pekanbaru, KPP Pratama Pekanbaru Tampan, and KPP Pratama Pekanbabru Senapelan. The data in this study is the primary data. The population in this study were the tax auditors who worked at KPP Madya Pekanbaru, KPP Pratama Pekanbaru Tampan, and KPP Pratama Pekanbabru Senapelan. The sampling method used in this study census method. The sample used in this study were 45 respondents. The method of data analysis used to the test the hypotesis is multiple regression analysis using SPSS version 21. The results of this study is showed that leadership style, professionalism, and job satisfaction influence on the tax auditors performance. The magnitude of the effect caused by Adjusted R² by three variables is 85% of the dependent variable, while the remaining 15% is influenced by other independent variabel that are not observed in this study.Keywords: leadership style, professionalism, job satisfaction, tax auditor performance